Descriptive Analysis of Employment In Azerbaijan: Possibilities of the Dutch Disease - Ibrahim Niftiyev (Journal of Economic Sciences: Theory & Practice, 2020)
This paper conducts a descriptive statistical analysis of employment in Azerbaijan covering the period between 2000 and 2018 to study the effects of the Dutch disease hypothesis. Azerbaijan has been a research subject of the Dutch disease due to the boom in the oil sector since independence from the Soviet Union. This paper bases its analysis on the descriptive statistics of employed persons per sector, its year on year growth dynamics, and cumulative growth rates. The results indicate that there are developments in employment that are in line with the spending effect of the Dutch disease model, as during the given time period, the mining sector did not experience sky-high employment, and manufacturing and agriculture shrank, though services increased their role. Moreover, constructed scatterplot matrix and conducted Pearson-s R correlation analysis shed light on the sectoral relationships among the critical economic variables like real effective exchange rate, oil prices, oil GDP, non-oil GDP, oil exports, and transfers from the sovereign wealth fund (SOFAZ), etc. However, the conclusions should be drawn with a significant extension of caution, as the descriptive investigation is extremely limited in terms of the identification of causal relationships.
Keywords: F41; F43; Q33; 330; Dutch disease; Azerbaijan economy; sectoral employment; descriptive statistics